(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the lexical and semantic features of oral communication in Russian. It analyzes the characteristic features of colloquial vocabulary, the semantic variability of words, and the influence of context and intonation on semantic interpretation. The role of diminutives, parentheses, and parasitic words in everyday speech is highlighted. The study emphasizes the importance of context and emotional connotation for effective communication. The results of the study have practical implications for linguists and educators studying and teaching Russian.